Analisis Prasasti Tumbu (Kajian Epigrafi) - Aris Kristianti, Made; Setiawan, I Ketut; Palupi Titasari, Coleta (Humanis; Vol 17 No 3 (2016), 2016)
Tumbu inscription is one of the cultural heritage in Tumbu Village, Karangasem District, Karangasem Regency. This inscription issued by one of the kings during Ancient Bali Period i.e Paduka Sri Maharaja Sri Bhatara Mahaguru Dharmmotungga Warmadewa in 1247 S aka (1325 AD). This study aimed at  describing the results of a study on the inscription of Tumbu related to the aspects of language and contents in Tumbu inscriptions as well as the public perception of  Tumbu village in relation to the existence of the inscriptions in their territory. The data collection methods applied in this research were observation, interviews and literature studies as well as data processing method through morphological and qualitative analysis. Some theories were applied such as the theory of structuralism, structural functionalism and power. Based on the analysis results it could be seen that the paleography aspect of Tumbu inscription used the ancient Javanese characters and  language. The contents in Tumbu inscription namely political aspects, economic aspects, and religious aspects. Meanwhile, the perception of Tumbu community about the existence of the inscription in their village that the inscription was the cultural heritage of their ancestor which was believed to provide welfare to the village and also an honor for them because their village has an inscription, so that the inscription was still preserved and sacred.